2013
DOI: 10.1007/s00426-013-0494-8
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of search, impasse, and representational change provide a coherent explanation of difficulty in the nine-dot problem

Abstract: The nine-dot problem is often used to demonstrate and explain mental impasse, creativity, and out of the box thinking. The present study investigated the interplay of a restricted initial search space, the likelihood of invoking a representational change, and the subsequent constraining of an unrestricted search space. In three experimental conditions, participants worked on different versions of the nine-dot problem that hinted at removing particular sources of difficulty from the standard problem. The hints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 25 publications
4
88
0
Order By: Relevance
“…Taken together, the data suggest that under no time restrictions, the ending location hint is likely to be stronger than that of the starting location hint. This assumption is in line with studies that showed that providing the key cue for a representational change can increase solution rates when the search space is adequately restricted (Kershaw & Ohlsson, 2004;Öllinger et al 2012;Öllinger, Jones & Knoblich, 2013). Moreover, the comparison between the 4to5 and the 5to4 conditions convincingly demonstrated that the main source of problem difficulty is to break the perceptual grouping, which was fostered by the "E" hints and not by the "S" hints.…”
Section: Strength Of Hintssupporting
confidence: 86%
See 3 more Smart Citations
“…Taken together, the data suggest that under no time restrictions, the ending location hint is likely to be stronger than that of the starting location hint. This assumption is in line with studies that showed that providing the key cue for a representational change can increase solution rates when the search space is adequately restricted (Kershaw & Ohlsson, 2004;Öllinger et al 2012;Öllinger, Jones & Knoblich, 2013). Moreover, the comparison between the 4to5 and the 5to4 conditions convincingly demonstrated that the main source of problem difficulty is to break the perceptual grouping, which was fostered by the "E" hints and not by the "S" hints.…”
Section: Strength Of Hintssupporting
confidence: 86%
“…The results provide further evidence for our dynamic constraint and representational change model (Öllinger, Jones & Knoblich, 2013), that postulates that a representational change is sometimes not sufficient to solve insight problems due to the fact that modifying a problem representation often results in an even larger problem space that has to be constrained by efficient search strategies. Recently, Lee and Johnson-Laird (2013) provided a more general model for strategy changes in problem solving and tested their assumptions by using matchstick problems that do not necessarily require insight.…”
Section: Strength Of Hintssupporting
confidence: 57%
See 2 more Smart Citations
“…This model underlies many subsequent and current models of human problem solving (Kaplan & Simon, 1990;Knoblich, Ohlsson, Haider, & Rhenius, 1999;Öllinger, Jones, & Knoblich, 2014;Ormerod, MacGregor, & Chronicle, 2002). In this model, a representation of a problem's givens and goals is chosen based on previous experience and search is then performed (possibly aided by heuristics) within the space of problem states associated with this representation until a state is encountered that satisfies the problem's goals, i.e., a goal state.…”
Section: Introductionmentioning
confidence: 99%